Silent periprocedural myocardial infarction during non-cardiac surgery: a case report - E. V. Ivanova; A. V. Arsentyev; M. K. Illarionova (Кардиоваскулярная терапия и профилактика)
Introduction. Diagnosis of silent coronary artery disease (CAD) in the early postoperative period is difficult. It is important to timely identify risk factors for cardiovascular complications before non-cardiac surgeries, which determines the optimal diagnostic and therapeutic strategy in the early postoperative period.Brief description. In the presented case report, the results of examination, diagnostic and treatment tactics of a 59-year-old female patient with type 2 diabetes, hypertension and risk factors for CAD after hip arthroplasty without probable CAD are assessed. The physical examination of the patient was assessed using clinical, functional and laboratory methods, and following scales: Revised Cardiac Risk Index (RCRI); Myocardial Infarction or Cardiac Arest (Gupta MICA); Caprini risk score/Caprini Risk Assessment Model; The Wells criteria for pulmonary embolism; Heavy, Hypertensive, Atrial Fibrillation, Pulmonary Hypertension, Elder, Filling Pressure (H2FPEF). The risk of cardiovascular complications according to the RCRI and Gupta MICA scores was assessed as low. During non-cardiac surgery of moderate risk with blood loss, the patient developed acute cardiovascular failure. Troponin-positive myocardial infarction was diagnosed without electrocardiographic and echocardiographic signs of impaired local contractility, against the background of atherosclerotic coronary stenosis, confirmed by coronary angiography.Conclusion. The case demonstrates the relevance of CAD probability assessment (pre-test, clinical) in patients with related risk factors during non-cardiac surgeries. According to Kashlan B, et al., the incidence of myocardial infarction after non-cardiac surgeries (2024) is 1%. Existing risk scores for periprocedural complications are not highly accurate and require meaningful application. The case is of interest to therapists, cardiologists, endocrinologists in relation to the preparation of a comorbid patient with CAD risk factors and the need to assess perioperative risks for an elective intervention with the achievement of recommended target indicators.